2007
DOI: 10.1016/j.yjmcc.2007.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of heart disease associated with murine and human GATA4 mutation

Abstract: The transcription factor GATA4 is essential for heart morphogenesis. Heterozygous mutation of GATA4 causes familial septal defects. However, the phenotypic spectrum of heterozygous GATA4 mutation is not known. In this study, we defined the cardiac phenotypes that result from heterozygous mutation of murine Gata4. We then asked if GATA4 mutation occurs in humans with these forms of congenital heart disease (CHD). In mice, heterozygous Gata4 mutation was associated with atrial and ventricular septal defect (ASD,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
187
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(197 citation statements)
references
References 33 publications
8
187
0
2
Order By: Relevance
“…Screening for mutations of SEMA3C and PLXNA2 may provide further evidence of the involvement of semaphorin-plexin signaling in human OFT defects. It is of note that GATA6 mutations identified in humans were associated with PTA, in contrast with GATA4 mutations, which are commonly associated with atrial and/or ventricular septal defects (20)(21)(22). This result suggests that GATA6 may play a dominant role in OFT development, although Gata6 has been reported to have a redundant role with Gata4 during cardiogenesis (25,(34)(35)(36).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Screening for mutations of SEMA3C and PLXNA2 may provide further evidence of the involvement of semaphorin-plexin signaling in human OFT defects. It is of note that GATA6 mutations identified in humans were associated with PTA, in contrast with GATA4 mutations, which are commonly associated with atrial and/or ventricular septal defects (20)(21)(22). This result suggests that GATA6 may play a dominant role in OFT development, although Gata6 has been reported to have a redundant role with Gata4 during cardiogenesis (25,(34)(35)(36).…”
Section: Discussionmentioning
confidence: 97%
“…Null mutation of Gata4 in mice results in embryonic lethality because of defects in cardiogenesis (18,19). Mutations of GATA4 in humans were identified to cause CHD characteristic of atrial and/or ventricular septal defects (20,21), and heterozygous mutations of Gata4 in mice recapitulate the human phenotype (22). Systemic ablation of Gata6 in mice also results in embryonic lethality (23), whereas conditional inactivation of Gata6 in the CNC results in perinatal mortality from OFT defects, typically PTA (24).…”
mentioning
confidence: 99%
“…During the course of this study, more germ line heterozygous GATA4 mutations have since been reported (Rajagopal et al 2007, Reamon-Buettner et al 2007. Interestingly, some of these occur in the GATA4 intronic sequences or the 3 0 non-translated region of the GATA4 mRNA.…”
Section: Discussionmentioning
confidence: 84%
“…Thus, far, only fully penetrant germ line GATA4 mutations have been reported as a result of screening large families where congenital heart defects are present in more than one generation. Recently, the screening of large cohorts of individuals presenting cardiac malformations uncovered the first non-fully penetrant GATA4 mutations (Rajagopal et al 2007. Given the identification of these novel GATA4 mutations, a similar screen of individuals presenting reproductive abnormalities, and especially that involving gonadal sex reversal is both warranted and needed.…”
Section: Discussionmentioning
confidence: 99%
“…The null mutation of GATA-4 results in the abnormal ventral folding of the embryo, failure to form a single ventral heart tube, and lethality by embryonic day (E) 10.5 (6,7). In humans, mutations in GATA-4 result in congenital cardiomyopathies, including valve and septal defects (8,9). Both conditional knockout mice lacking GATA-4 in specific cardiomyocytes, as well as transgenic mice expressing only 30% of the normal levels of GATA-4 in the heart, display atrioventricular canal defects and a hypoplastic ventricular myocardium.…”
Section: Introductionmentioning
confidence: 99%